Detection and statistic analysis of formal error spelling in Indonesian - Erwina, Emmy; Tommy, Tommy; Mayasari, Mayasari (Edelweiss Applied Science and Technology, 2025)
Using language with correct pronunciation, especially for teachers and lecturers, can help foster language awareness among the younger generation. The high use of non-standard language and incorrect pronunciation of words in the younger generation is a serious concern, considering that culture and trends in the current era of globalization have caused language standards to fade. This study detects and classifies errors in the pronunciation of standard words in Indonesian, using teachers at the teacher level and lecturers at the Yayasan Pendidikan Harapan Medan as respondents. The data on the classification of pronunciation errors were obtained from the respondents' teaching video recordings. The detection results showed that the most common pronunciation errors made by the respondents were vowel errors, accounting for 59.8%, followed by consonant errors at 25.2%, and diphthong errors at 15%. Statistical analysis indicates that the type of teacher attribute influences the pronunciation errors made. The teacher's age attribute has the least effect on pronunciation errors.